2019
DOI: 10.21203/rs.2.10436/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interventions to Improve Discharge from Acute Adult Mental Health Inpatient Care to the Community: Systematic Review and Narrative Synthesis

Abstract: Background The transition from acute mental health inpatient care to community care is often a vulnerable period in the pathway, where people can experience additional risks and anxiety. Researchers globally have developed and tested a number of interventions that aim to improve continuity of care and safety in the transitions. However, there has been little attempt to compare and contrast the interventions and specify the variety of safety threats they attempt to resolve.Methods The study aimed to identify … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
(145 reference statements)
0
9
1
Order By: Relevance
“…Moreover, international studies have been mainly concentrated on the effects of specific transitional interventions after discharge from inpatient psychiatric facilities 21,22 , but we did not find evidences on patients' outcomes after a follow-up period, in a mental health setting based on longitudinal continuity of care. In a previous study from the region 23 , we observed that both CA and VA patients improved during hospitalisation.…”
Section: Introductioncontrasting
confidence: 57%
“…Moreover, international studies have been mainly concentrated on the effects of specific transitional interventions after discharge from inpatient psychiatric facilities 21,22 , but we did not find evidences on patients' outcomes after a follow-up period, in a mental health setting based on longitudinal continuity of care. In a previous study from the region 23 , we observed that both CA and VA patients improved during hospitalisation.…”
Section: Introductioncontrasting
confidence: 57%
“…Prior research on transition planning interventions among psychiatric patient populations suggests that discharge planning is key to preventing readmission [8]. Existing literature cites collaborative care between inpatient staff, psychoeducation for patients and caregivers, communication between inpatient and outpatient networks, and medication reconciliation as important pieces of effective discharge and transition planning interventions [15][16][17]. Therefore, the PODS tool for medical discharge was modified at the Centre for Addiction and Mental Health (CAMH), a tertiary care psychiatric hospital in Ontario, Canada, to suit the informational needs of individuals transitioning from psychiatric hospital to the community.…”
Section: Introductionmentioning
confidence: 99%
“…International researchers were invited to participate whether they had published a peer‐reviewed paper in a previous systematic review, 50 researchers were invited 15 . Twenty‐nine British end users of research were identified using publicly accessible contact details and individually invited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple systems‐level risk factors for safety have been found in mental health‐care transitions, namely the lack of continuity of care, co‐ordination and communication difficulties between organizations and professionals 6‐9 . Various interventions have been developed to improve safety in mental health services 10‐14 but very few explicitly describe an underlying theory of change 15 . Yet it is increasingly recognized that the evaluation of quality improvement interventions, such as those for hospital discharge, should more overtly articulate and appraise the underpinning theory of change for a given intervention (the rationale and assumptions about mechanisms that links processes and inputs to outcomes, also specifying the conditions necessary for effectiveness) 16,17 .…”
Section: Introductionmentioning
confidence: 99%